2020
DOI: 10.1002/agj2.20400
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and physiological responses of Cannabis sativa to an integrated plant nutrition system

Abstract: The illegal status of cannabis (Cannabis sativa L.) post-World War II resulted in a lack of research on agricultural practices. However, there is a resurgence of interest in cannabis due to diverse uses such as a rich source of cellulosic/woody fiber and construction uses, seed oil, bioenergy and pharmaceutical properties. The principle of an integrated plant nutrition system (IPNS) is to enable adaptation of plant nutrition and soil fertility management to local site characteristics, attempting to optimize us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…The combination of both mineral and organic fertilizers for integrated crop nutrition as performed in our study and also cited in the literature ( Bernstein et al., 2019 ; Da Cunha Leme Filho et al., 2020 ; Laleh et al., 2021 ) suggests that the higher availability of mineral fertilizer can be important for plant initial growth, while organic fertilizers can be employed as a more sustainable nutrient complementation during flowering without major yield losses. It is relevant to further investigate the effects of nutrient deprivation in the different stages of flowering, as the major balance between biomass accumulation and the concentration of secondary metabolites can be modulated.…”
Section: Discussionsupporting
confidence: 69%
“…The combination of both mineral and organic fertilizers for integrated crop nutrition as performed in our study and also cited in the literature ( Bernstein et al., 2019 ; Da Cunha Leme Filho et al., 2020 ; Laleh et al., 2021 ) suggests that the higher availability of mineral fertilizer can be important for plant initial growth, while organic fertilizers can be employed as a more sustainable nutrient complementation during flowering without major yield losses. It is relevant to further investigate the effects of nutrient deprivation in the different stages of flowering, as the major balance between biomass accumulation and the concentration of secondary metabolites can be modulated.…”
Section: Discussionsupporting
confidence: 69%
“…Humic acid supplementation had a positive effect on cannabis in the case of the height of cannabis plants, the chlorophyll content and the efficiency of photosynthesis, especially immediately after the period of water stress (Da Cunha Leme Filho et al 2020).…”
Section: Plant Biostimulantsmentioning
confidence: 97%
“…Similarly, the use of biofertilizer increased plant height on pomegranate ( Punica granatum L.) (Aseri et al 2008 ) and sunflower ( Helianthus annus L.) (Akbari et al 2009 ). On cannabis, Conant et al ( 2017 ) and Da Cunha Leme Filho et al ( 2020a , b ) reported greater cannabis height due to biostimulant applications under indoor conditions.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As soil CO 2 evolution is directly related to soil microbial activity (Frankenberger Jr and Dick 1983 ), the application of HA positively affects microbial growth due enzymatic function (Visser 1985 ) and carbon source (Flaig 1964 ). A review evaluating the effects of HA on microbial activity indicated that HA dose and bacteria and fungi species have an important influence on whether or not the activity measurement will be increased (Da Cunha Leme Filho et al 2020a , b ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation